An ethnobotanical study of traditionally used medicinal plants: Case study from Assam, India - Kalita, Meghali; Alam, Saklain Mustak; Jelil, Shah Nawaz (Ethnobotany Research and Applications, 2024)
Background: Traditional knowledge of medicinal plants, their application, and conservation is very likely to be disappearing. From the perspective of conservation planning and management, it is crucial to assemble information about the use of medicinal herbs by various ethnic groups and at various spatial scales. Therefore, with this viewpoint in mind, this study was carried out, which included the ethnobotanical analysis of medicinal plants in Dimoria, Assam, which contributed to the locally based traditional healthcare system of the people living there. Methods: The study was conducted with 140 traditional knowledgeable people (78 male and 62 female) being interviewed purposively. Household questionnaire surveys (HQS), key informant interviews (KII), and focus group discussions (FGD) were used for data collection. The use value (UV) score of species, informant consensus factor (ICF), and fidelity level (FL) were computed as standard ethnobotanical data analytical methods. Results: The current study compiled information on the traditional use of 80 plant species from 45 different botanical groups to treat 56 distinct human diseases. The families that have the most species were Fabaceae followed by Rutaceae, Lamiaceae, Acanthaceae, Amaranthaceae, etc. Leaves (60%) were found the most commonly used plant parts for the treatment of various health ailments. The average UV score was found to be 0.64 (0.40 – 0.89). Based on UV scores, the most used species was Zingiber officinale (UV 0.89) and the least used species were Cereus repandus (UV 0.40). The FL of plant species ranged from 67.09 % to 94.44 % for the eleven categories chosen in the study area. The maximum FL of 94.44 % was found for Azadirachta indica for the dermatological disorder category. In our study, ICF factors for each category of usage ranged from 0.69 to 0.94, with cardiovascular disorder exhibiting the highest ICF value of 0.94. Conclusions: The results of the study demonstrated that Dimoria is a repository for indigenous knowledge and a highly varied range of reliable plant species. Furthermore, additional research is required to determine the safety and efficacy of described ethnomedicinal plants in treating a variety of diseases, as the findings presented in this paper are preliminary in nature. As a result, the study highlights the potential of ethnomedical research as well as the significance of recording customary knowledge about the use of medicinal plants by the community for the benefit of all people. Keywords: Ethnobotany; Indigenous; Medicinal plants; Traditional knowledge; Assam